Socio-Spatial Segregations in Social Media - UZUNÇARŞILI SOYDAŞ, AYDA (EDICIONES UNIV SALAMANCA, 2016)
In conjunction with developments in communication technologies, life spaces of people also change and develop. What constitutes the most important building block of these new life spaces are digital communication resources. Digital communication resources form new spaces in social media by manipulating identities and cultures. These new spaces create socio-spatial segregations, whether consciously or unconsciously. Especially in recent years, grouping is observed intensely in social media and from time to time these groups play an important role in mass actions. In this study, closed and secret groups formed in social media were examined, with qualitative and quantitative research methods. Within this context, through in-depth interviews with group admins and survey study with group members, socio-spatial segregation in social media and grouping processes in social media were examined.
Keywords: Social Media; socio-Spatial Segregation; grouping; Digital Urbanization; facebook groups